Harvesting easter eggs: An exploratory study of enjoying transnarrative media - Judy Watts; Hannah Wing (PLoS ONE, 2026)
Transnarrative storytelling, or fragmented narratives, has been undertheorized yet is increasingly more common in entertainment. An exploratory study guided by entertainment enjoyment theories explored potential predictors of enjoyment from transnarrative stories. A retrospective survey (n = 956) utilized both close- and open-ended measures and found parasocial relationships and fan behaviors (e.g., internet searches, discussions) were positively associated with intrinsic rewards and enjoyment. Intrinsic rewards were also positively associated with enjoyment above and beyond PSR and fan behaviors. Emerging themes from open-ended questions suggest that easter eggs are discovered by audiences when characters, objects, events/actions, and other forms of entertainment appear. Lastly, participants who found easter eggs described their responses as excited, happy, and full of pride. Implications include the necessity for additional research on transnarrative media processing.